Impaired olfactory function in bipolar disorder patients during acute episodes regardless of psychotic symptoms - Li, Yingying; Yuan, Huiqian; Liu, Xianlin; Su, Langjun; Yang, Chunhong; Chen, Chao; Li, Chunyang (Frontiers in Psychiatry, 2023)
The aim of this study was to analyze whether the presence of psychotic symptoms affects olfactory function in patients with bipolar disorder (BD). We also compared olfactory function between the period of episode and remission in patients with BD.Methods: BD patients in the acute phase were tracked to the remission stage. The psychiatric symptoms and social function of the enrolled subjects were assessed using the Hamilton Rating Scale for Depression (HAMD), the Young Mania Rating Scale (YMRS), the Hamilton Rating Scale for Anxiety (HAMA), the Positive and Negative Syndrome Scale (PANSS) and the Global Assessment Function (GAF). Olfactory sensitivity (OS) and olfactory identification (OI) was assessed using the Sniffin' Sticks test. Differences in OS and OI among the episodic group, the euthymic group, and the healthy control (HC) group were compared. According to whether BD is accompanied by psychotic symptoms, the OS and OI in the BD with psychotic symptoms group (P-BD), the BD without psychotic symptoms group (NP-BD), and the HC group were compared.The P-BD and NP-BD groups exhibited impaired OI compared with the HC group, but there was no significant difference in OI between the P-BD and NP-BD groups, or in OS among all three groups. All patients with episodic BD had significantly lower OS and OI compared with the HC group. OI in euthymic BD patients was still impaired; however, OS recovered, showing no significant difference compared with that in the HC group.The results indicate that patients with episodic BD have impaired OS and OI, regardless of psychotic symptoms. OI may be a characteristic marker of BD, and OS may be a state marker that can be used to distinguish between episodic and euthymic BD.